Effect of Ethical Leadership on Workplace Cyberbullying Exposure and Organizational Commitment - Tiamboonprasert, Worakamol; Charoensukmongkol, Peerayuth (The Journal of Behavioral Science, 2020)
Cyberbullying is a significant and prevalent problem in Thai society. Although research about cyberbullying has been conducted among teenagers and employees at private organizations, there remains a research gap regarding the issue of cyberbullying in educational institutions, particularly the antecedent and outcome associated with it. The present study investigates the effect of ethical leadership on employees’ exposure to workplace cyberbullying at one public university in Thailand. Theoretically, the role of ethical leadership is based on the Emotion Reaction Model. Survey data were collected from 358 employees using stratified sampling. The results from Partial Least Squares Structural Equation Modeling support the effect of ethical leadership on cyberbullying exposure (β= -.20, p < 0.01), as well as the effect of cyberbullying exposure on organizational commitment (β= -.25, p < 0.01). Additionally, the scope of usage for the computer-mediated communication (CMC) platform significantly moderates the effects of ethical leadership on cyberbullying exposure (β = -.14, p < 0.01) as well as the effect of cyberbullying exposure on organizational commitment (β = -.16, p < 0.01). This research provides two related implications. Firstly, it is crucial to understand that cyberbullying can happen easily when employees use various CMC platforms in the university. Secondly, although it is inevitable to regulate employees’ use of CMC, the role of the supervisor’s ethical leadership plays a vital role in creating the supportive and ethical climate in the work units to prevent the chance that someone will utilize the technology to cyberbullying other employees.